Penerapan Metode Simple Additive Weighting (SAW) untuk Penentuan Muazin Terbaik - Harman, Rika; Amrizal, Amrizal; Rosiska, Evan (Universitas Merdeka Malang, 2023)
Decision-making is sometimes often wrong so it can harm certain parties. If the decisions taken are very strategic, you can imagine the losses that will result from these decisions. The Al-Hikmah Mosque, which is located at the Taman Hangtuah Legenda Malaka Batam Center housing complex, is currently experiencing a muezzin vacancy. Al-Hikmah Mosque itself has held a selection for the muezzin. From the selection results, the five best people were obtained. Of the five best people, one will be selected and meets the criteria. The purpose of this research is to make it easier for the Al-Hikmah mosque to make decisions to get the best of the best muezzins. In addition, the mosque can also get choices if the first choice resigns. In this study, the method used is Simple Additive Weighting (SAW) where all participants who meet the criteria will be ranked. The results of the ranking, who were selected to be the best muezzin with the best value or rank were Mr. Abdul Hafiz with a score of 0.845, and Mr. Ihsan as the second alternative with a value of 0.7925. From the results of this study, it can be concluded that the Simple Additive Weighting (SAW) method in determining the best muezzin has a high degree of accuracy. This can prevent discrimination because the election system is based on logically processed data so that all participants can accept the results obtained.